Reduced Activity of Geranylgeranyl Reductase Leads to Loss of Chlorophyll and Tocopherol and to Partially Geranylgeranylated Chlorophyll in Transgenic Tobacco Plants Expressing Antisense RNA for Geranylgeranyl Reductase - Tanaka, Ryouichi (American Society of Plant Physiologists, 1999)
The enzyme geranylgeranyl reductase (CHL P) catalyzes the reduction of geranylgeranyl diphosphate to phytyl diphosphate. We identified a tobacco (Nicotiana tabacum) cDNA sequence encoding a 52-kD precursor protein homologous to the Arabidopsis and bacterial CHL P. The effects of deficient CHL P activity on chlorophyll (Chl) and tocopherol contents were studied in transgenic plants expressing antisense CHL P RNA. Transformants with gradually reduced Chl P expression showed a delayed growth rate and a pale or variegated phenotype. Transformants grown in high (500 μmol m(−2) s(−1); HL) and low (70 μmol photon m(−2) s(−1); LL) light displayed a similar degree of reduced tocopherol content during leaf development, although growth of wild-type plants in HL conditions led to up to a 2-fold increase in tocopherol content. The total Chl content was more rapidly reduced during HL than LL conditions. Up to 58% of the Chl content was esterified with geranylgeraniol instead of phytol under LL conditions. Our results indicate that CHL P provides phytol for both tocopherol and Chl synthesis. The transformants are a valuable model with which to investigate the adaptation of plants with modified tocopherol levels against deleterious environmental conditions.